Evaluation of Left Ventricular Outflow Tract Obstruction With Four-Dimensional Phase Contrast Magnetic Resonance Imaging in Patients with Hypertrophic Cardiomyopathy—A Pilot Study. Issue 6 (November 2016) - Chu, Linda C.; Porter, Kristin K.; Corona-Villalobos, Celia Pamela; Gülsün, Mehmet Akif; Shea, Steven M.; Markl, Michael; Abraham, Theodore P.; Bluemke, David A.; Kamel, Ihab R.; Zimmerman, Stefan L.
Abstract : Objective: This study aimed to validate 4-dimensional phase contrast (4D PC) cine magnetic resonance imaging (MRI) as a means of evaluating left ventricular outflow tract (LVOT) obstruction in patients with hypertrophic cardiomyopathy (HCM). Methods: In this institutional review board-approved prospective study, 23 patients with suspected HCM from October 2012 to September 2013 underwent 4D PC MRI. Postprocessed 4D PC pathline cine data were reviewed by 2 blinded reviewers to determine presence or absence of LVOT obstruction. Sensitivity, specificity, and accuracy in 4D PC qualitative and quantitative assessment of LVOT obstruction were calculated using echo as reference standard. Results: Consensus interpretation of 4D PC showed 100.0% (7/7) sensitivity, 75.0% specificity (12/16), and 82.6% (19/23) accuracy in assessment of LVOT obstruction. The 4D PC quantitative estimates of LVOT gradient have 71.4% (5/7) sensitivity, 93.8% (15/16) specificity, and 87.0% (20/23) accuracy in evaluation of LVOT obstruction compared with echo. Conclusions: The 4D PC MRI can assess for LVOT obstruction in HCM patients. Abstract : Supplemental digital content is available in the text.